Taxonomic study on the leafhopper genus Cofana Melichar (Hemiptera: Cicadellidae: Cicadellinae) from China, with description of two new species - Yang, Mao-Fa; Meng, Ze-Hong; Li, Zi-Zhong (Zootaxa, 2015)
A review of the genus Cofana Melichar from China is presented. Ten species are recorded, of which two species are new: C. cheni sp. nov. and C. nii sp. nov. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC). In this paper, C. bidentata Krishnankutty & Viraktamath, 2008 is placed as junior synonym of C. yasumatsui Young, 1979. A key of all Chinese species of the genus is provided.